Association of the EPAS1 gene G/A polymorphism with successful performance in a group of Russian wrestlers - E. A. Bondareva; E. Z. Godina (Вавиловский журнал генетики и селекции)
A large number of studies showed that the gene EPAS1 may serve as a possible predictor of success in sports because of its influence on the processes of oxygen transportation and consumption. However, data concerning the impact of EPAS1 polymorphisms on sports achievements in the modern research literature are very scarce and contradictory. The aim of the present paper was to study genetic selection in the polymorphic system of the EPAS1 gene (rs1867785) in a group of male sambo practitioners. 312 Russian males from 18 to 30 years of age were studied. Of them, 220 were professional athletes and 92 were non-athletes, who served as the control group. The genotype of a single nucleotide G/A polymorphic system of the EPAS1 gene was determined for each participant of the study. Analysis of genotype frequencies revealed statistically significant differences between the two groups. An increase of АА and AG genotype frequencies was revealed in the group of athletes (χ2 = 8.68, p = 0.01). Thus, for sambo practitioners, who reached high levels, the presence of the minor А-allele in the genotypes was typical. The odd ratio (OR) calculated for this group was 1.800 (95 % CI 1.227–2.641), demonstrating that the carriers of the А-allele of the EPAS1 gene had some advantages over the carriers of the G-allele. OR for the highest-rank wrestlers was even higher, 1.990 (95 % CI 1.195–3.313). These results suggest directed genetic selection in the А-allele carriers of the EPAS1 gene among sambo practitioners.